2012
DOI: 10.1111/j.1476-5381.2011.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and bone: endocannabinoids modulate human osteoclast function in vitro

Abstract: BACKGROUND AND PURPOSEBoth CB1 and CB2 cannabinoid receptors have been shown to play a role in bone metabolism. Crucially, previous studies have focussed on the effects of cannabinoid ligands in murine bone cells. This study aimed to investigate the effects of cannabinoids on human bone cells in vitro. EXPERIMENTAL APPROACHQuantitative RT-PCR was used to determine expression of cannabinoid receptors and liquid chromatography-electrospray ionization tandem mass spectrometry was used to determine the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…CB-1 receptors are predominantly located in the central nervous system, whereas CB-2 receptors are expressed in the immune system, cirrhotic liver, arteriosclerotic plaques, gastrointestinal mucosa and during brain inflammation (9)(10)(11). CB-2 receptors have also been reported to have a significantly higher expression in osteoblasts, osteoclasts and osteocytes compared to CB-1 receptors (12)(13)(14). Therefore, specific CB-2 agonists/antagonists could be involved in the regulation of bone remodeling as a result of their effects on osteoblasts and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…CB-1 receptors are predominantly located in the central nervous system, whereas CB-2 receptors are expressed in the immune system, cirrhotic liver, arteriosclerotic plaques, gastrointestinal mucosa and during brain inflammation (9)(10)(11). CB-2 receptors have also been reported to have a significantly higher expression in osteoblasts, osteoclasts and osteocytes compared to CB-1 receptors (12)(13)(14). Therefore, specific CB-2 agonists/antagonists could be involved in the regulation of bone remodeling as a result of their effects on osteoblasts and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…8 CB 1 and CB 2 receptors are found in many tissues in mammals, 4 including the bone cells of human 9 and mouse 10 species. WIN-55,212-2 is a synthetic cannabinoid that binds to both CB 1 and CB 2 receptors and had been demonstrated to impede angiogenesis, induce apoptosis in mouse cancer cells, 9 and inhibit VEGF expression in both human and mouse cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…WIN-55,212-2 is a synthetic cannabinoid that binds to both CB 1 and CB 2 receptors and had been demonstrated to impede angiogenesis, induce apoptosis in mouse cancer cells, 9 and inhibit VEGF expression in both human and mouse cancer cells. 11,12 Cancer biology and tumor behavior have been shown to be similar in humans and dogs for several common cancers, 13 and the dog is emerging as a valuable naturally occurring cancer model.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 A number of recent studies reported that AEA and 2-AG together with their metabolizing enzymes are present in the skeleton within the trabecular compartment, and both osteoblasts and osteoclasts were reported to produce both endocannabinoids in vitro. [9][10][11][12] A growing list of synthetic non-classical cannabinoid receptor agonists such as CP55,940, JWH133 and HU308 and inverse agonists/antagonists, including SR141716A (also known as Rimonabant or Acomplia), AM251 and AM630 were reported to influence bone cell differentiation and activity in vitro and bone turnover in mouse models of bone disease ( Table 1). [11][12][13][14][15][16][17][18][19] Endocannabinoids and their related ligands activate two classic cannabinoid receptors, cannabinoid type 1 receptor (CB1) and type 2 (CB2), both of which are members of the G protein-coupled receptor (GPR) family coupled to adenylyl cyclase and cyclic adenosine monophosphate.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] A growing list of synthetic non-classical cannabinoid receptor agonists such as CP55,940, JWH133 and HU308 and inverse agonists/antagonists, including SR141716A (also known as Rimonabant or Acomplia), AM251 and AM630 were reported to influence bone cell differentiation and activity in vitro and bone turnover in mouse models of bone disease ( Table 1). [11][12][13][14][15][16][17][18][19] Endocannabinoids and their related ligands activate two classic cannabinoid receptors, cannabinoid type 1 receptor (CB1) and type 2 (CB2), both of which are members of the G protein-coupled receptor (GPR) family coupled to adenylyl cyclase and cyclic adenosine monophosphate. [20][21][22] CB1 receptors are expressed primarily on neurons in the brain, spinal cord and peripheral nervous system, 23 but they are also found in the spleen, tonsils, immune cells, reproductive tissues, gastrointestinal tissues, heart, lung and adrenal gland.…”
Section: Introductionmentioning
confidence: 99%